2002
DOI: 10.1097/00007632-200209150-00008
|View full text |Cite
|
Sign up to set email alerts
|

Spine Deformity Correction in Marfan Syndrome

Abstract: The cardiopulmonary condition of patients with Marfan syndrome should be evaluated and planned for before surgery. Preoperative computed tomograph to assess bony adequacy for fixation and magnetic resonance imaging to evaluate dural ectasia are indicated. Attention paid to the sagittal profile, extension of fusion to vertebrae neutral and stable in both planes, minimization of soft tissue dissection, and avoidance of extreme correction may prevent curve decompensation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(61 citation statements)
references
References 35 publications
1
60
0
Order By: Relevance
“…4,16,17 The diagnosis of infection is difficult to establish but is suggested by pain, 18 the presence of a sinus tract, persistent or late postoperative wound drainage, erythema, wound dehiscence, positive culture from a wound aspirate, instrumentation failure/pseudoarthrosis and pathologic confirmation of the presence of inflammatory cells and/or the offending organism(s). 1,3,5,6,19 Staphylococcus aureus 1,12,15 and S. epidermidis 2,5,20 have been reported to be the most common causative organisms. A high erythrocyte sedimentation rate (ESR) has also been reported to be associated with late infection.…”
mentioning
confidence: 99%
“…4,16,17 The diagnosis of infection is difficult to establish but is suggested by pain, 18 the presence of a sinus tract, persistent or late postoperative wound drainage, erythema, wound dehiscence, positive culture from a wound aspirate, instrumentation failure/pseudoarthrosis and pathologic confirmation of the presence of inflammatory cells and/or the offending organism(s). 1,3,5,6,19 Staphylococcus aureus 1,12,15 and S. epidermidis 2,5,20 have been reported to be the most common causative organisms. A high erythrocyte sedimentation rate (ESR) has also been reported to be associated with late infection.…”
mentioning
confidence: 99%
“…To date, only three series have been published [2][3][4]. It has been shown that the natural history of the scoliosis associated with MFS is unique and does not resemble that in AIS; it is often more severe [2] in MFS patients, and the King's guidelines used to determine the extent of the arthrodesis in AIS [16,17] does not fit the scoliosis associated with MFS [5][6][7]. A subset of patients with both juvenile and adolescent ''idiopathic'' scoliosis may have an underlying condition that may cause the scoliosis.…”
Section: Discussionmentioning
confidence: 99%
“…This is the ratio between the dural sac diameter (DSD) measured on the midline sagittal image and the vertebral body diameter (VBD) at the same level (63). Further signs include scalloping of the vertebrae, and perineural or Tarlov cysts (cystic dilation containing spinal fluid along the nerve root) (64).…”
Section: Diagnosismentioning
confidence: 99%